Celebrating Guadalupe - Dunnington, Jacqueline Orsini (Rio Nuevo Publ., 2004)
She is everywhere -- The 1531 legend -- The San Juan Diego story -- Guadalupe's history and the miraculous portrait -- Guadalupe today -- Guadalupe and the author